The Contribution of Chaplaincy to Primary and Community Care: A Semi-Structured Interview Study With Clients - Annelieke Damen; Carmen Schuhmann; X.J.S. Rosie; Marjo van Zundert; Gaby Jacobs; Hanneke Muthert; Erik Olsman; Anja Visser (Journal of Primary Care & Community Health)
Introduction: A broad range of studies have associated spirituality with health outcomes. However, the integration of spiritual care in primary and community care has substantially lagged behind. Chaplains, as specialist spiritual caregivers, are increasingly employed in primary and community care to fill the gap. To investigate the implementation of chaplains in these settings from the perspective of clients, this study focused on the following research question: what are primary and community care clients’ reasons to seek chaplaincy care, their ideas of care goals, and what outcomes of care do they report? Methods: 24 Dutch chaplaincy clients were interviewed. Results: Clients sought support from a chaplain for existential concerns, or an existential struggle encompassing several areas of life. They described goals and outcomes of care in 3 domains: (1) the relationship with the chaplain, which included being seen, heard and acknowledged; (2) meaning-making, where they gained insight into and/or processed life-events, and connected more with themselves, others and/or the sacred; and (3) well-being, which included feeling better and finding peace. Conclusions: This study provides novel insights into clients perspective on chaplains’ contributions in primary and community care. Their experiences are key to further shaping the implementation of chaplaincy in these settings.